Relationship Between Spermatid Specific Thioredoxin-3 Protein and Antisperm Antibody in Patients with Varicocele Compared with a Control Group - Ameer Ali Imarah1 , Waleed A.H.2 (Indian Journal of Forensic Medicine & Toxicology, 2021)
The spermatogenesis process are very complex and involves many process to lead to give normal sperm, these sperms a very important to fertility in the men). Protein in the male fertility that is very importantwhich give the significant job in fertilization. The infertile varicocele patient grade 1,2 and 3 (n= 25 , 25and 25 respectively) compare with control patient (n=15). The present study Shown spermatid – specificthioredoxin 3 level a significant increase in varicocele patient grade 1,2 and 3 compare with control group(mean± Std. Error 17.97± 0.8 & 22.92±0.75 Respectively) .Also in Antisperm antibody a significant increasein varicocele patient grade 1,2 and 3 compare with control group (mean± Std. Error 73.85±2.71 & 45.6±1.44Respectively ). Consecutive (r= -0. 840, r = -0. 745 and r = -0. 475). Also theirs a negative correlationbetween Antisperm antibody level and the sperms concentration , Sperm Progressive motility percent andsperm normal morphology present in varicocele patient grade 1,2 and 3 Consecutive (r= -0.443 , r = -0.370and r = -0.384 ) .The result show a positive correlation was found between Spermatid specific thioredoxin-3 protein leveland antisperm antibody level in varicocele patients .(The present study conclude that a negative function ofSpermatid specific thioredoxin-3 protein and antisperm antibody which that appears on sperm function andsperm parameters , The study showed that spermatid specific thioredoxin-3 protein and antisperm antibodyhas a harmful effect with the time) .